2019
DOI: 10.1128/mcb.00194-19
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2 Binding to H4K20me2 via a Methyl-Binding Domain Is Essential for Efficient DNA Cross-Link Repair

Abstract: Fanconi anemia (FA) is an inherited disease characterized by bone marrow failure and increased cancer risk. FA is caused by mutation of any 1 of 22 genes, and the FA proteins function cooperatively to repair DNA interstrand cross-links (ICLs). A central step in the activation of the FA pathway is the monoubiquitination of the FANCD2 and FANCI proteins, which occurs within chromatin. How FANCD2 and FANCI are anchored to chromatin remains unknown. In this study, we identify and characterize a FANCD2 histone-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…We have previously performed a CRISPR-Cas9 screening with MM and KMM cells and identified genes that promote or suppress cell proliferation and survival ( 21 ). By combining the EpiFactors database ( 4 ) and the epigenetic factors newly described between 2015 and 2021 ( 26 , 29 33 ), we identified 701 epigenetics-related genes that had differential effects on cell proliferation and survival between MM and KMM cells following their knockout ( Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously performed a CRISPR-Cas9 screening with MM and KMM cells and identified genes that promote or suppress cell proliferation and survival ( 21 ). By combining the EpiFactors database ( 4 ) and the epigenetic factors newly described between 2015 and 2021 ( 26 , 29 33 ), we identified 701 epigenetics-related genes that had differential effects on cell proliferation and survival between MM and KMM cells following their knockout ( Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…DNA binding of FANCI–FANCD2 is required for monoubiquitination and activation of the FA signaling. Despite the numerous important findings, such as that FANCD2 binding to H4K20me2 is essential for repairing DNA crosslinks [ 62 ], how this activates DNA repair remains largely unclear. In addition, our studies on FANCD2 variants demonstrate an in-depth understanding of how FA signaling is timely in guarding genome stability, which may bring promising biomarkers that are useful for cancer prevention and/or earlier cancer diagnosis.…”
Section: The Center or Focal Point Of Fa Signalingmentioning
confidence: 99%
“…FANCD2 binds to H4K20me2 via its histone-binding domain (HBD) and an embedded methyl-lysine-binding domain (MBD). A HBD/MBD mutant of FANCD2 that can be efficiently monoubiquitinated demonstrates impaired chromatin binding and foci formation, suggesting that monoubiquitination precedes ICL recruitment of FANCD2 [46]. However, arguing against this time course are studies that showed the ID2 complex is recruited to ICLs before the occurrence of FANCD2 monoubiquitination [41].…”
Section: Unhooking and Translesion Synthesis (Tls)mentioning
confidence: 99%